Human trafficking, human misery: the global trade in human beings - Aronowitz, Alexis A. (Global crime and justice, 2009)
Virtually all countries in the world are affected by the scourge of human trafficking, either as a source, transit, or destination country, or combination thereof. While countries have long focused on international trafficking, internal movement and exploitation within countries may be even more prevalent than trans-border trafficking. Patterns of trafficking vary across countries and regions and are in a constant state of flux. Countries have long focused on trafficking solely for the purpose of sexual exploitation, yet exploitation in agriculture, construction, fishing, manufacturing, and the domestic and food service industries is prevalent in many countries